Excited-state properties of Y-series small molecule semiconductors. (August 2021) - Wen, Guanzhao; Hu, Rong; Su, Xiaojun; Chen, Zhifeng; Zhang, Chengyun; Peng, Jun; Zou, Xianshao; He, Xiaochuan; Dong, Geng; Zhang, Wei
Abstract: The emergence of the Y series small molecule semiconductors, Y6 and its derivatives, have significantly improved the performance of polymer solar cells (PSCs). However, the excited-state properties of these Y-series small molecule semiconductors which are highly important for designing high-performance PSCs, need to be illustrated. In this work, the excited-state properties and electronic structures of the Y-series small molecules (Y5, Y6, Y10, N3, Y6-BO-4F, and Y6-BO-4Cl) have been systematically studied by using steady-state and time-resolved spectroscopies and quantum chemical calculations. It is shown that the influence of alkyl chains at the nitrogen atom of the pyrrole ring is weak for the electron affinities, ionization potentials, electron and hole reorganization energies and singlet exciton lifetime of Y molecules. Meanwhile, these parameters are found to be varied with the types of electron-deficient termini. Moreover, we find that Y10 and Y5 have the shortest singlet exciton lifetime in solution and the longest singlet exciton lifetime in film (~1100 ps), suggesting the engineering of electron-deficient termini can significantly influence the excited-state lifetime in solution and film. Our work could provide a guideline for designing Y-series acceptor materials for high-performance polymer solar cells. Graphical abstract: Image 1 Highlights: Effects of alkyl-chain and termini engineering on the excited state properties of Y molecules were studied. The influence of alkyl-chain engineering at the nitrogen atom is weak for singlet exciton lifetime of Y molecules. Termini engineering can significantly influence electron reorganization energies and excited-state lifetime of Y molecules. Y10 and Y5 show the shortest singlet exciton lifetime in solution and the longest singlet exciton lifetime in film.